Dongeng Sebagai Sosialisasi Mitigasi Bencana Kebakaran di Pemukiman Padat Penduduk Kelurahan Petukangan Utara, Pesanggrahan Jakarta Selatan - Dian Tri Hapsari; Uljanatunnisa Uljanatunnisa (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2020)
DKI Jakarta is the capital of the Republic of Indonesia which has a great risk of fire disasters in densely populated settlements, especially during the long dry season. Petukangan Utara Village, Pesanggrahan Subdistrict, South Jakarta, one of the pockets of dense settlements in the South Jakarta area that was targeted by the community service locations. The area of Petukangan Utara 2.99 Km2 consists of 5,075 families with 119 RTs and 11 RWs. The impact of settlement density has been a source of reduced number of infiltration wells and loss of water discharge around the settlement thereby increasing the risk of fire in dense residential areas. However, the high risk of fire disaster is not accompanied by a strong briefing on disaster mitigation. During this time, the community carries out more post-disaster activities in the form of emergency response and recovery rather than pre-disaster activities in the form of disaster reduction / mitigation and disaster preparedness as in neighboring countries. So the community service program focuses on the development of disaster mitigation, especially fire disasters with the goal of questioning children through reading fairy tales. The activity partner is Rumah Yatim Nurul Hasanah in the densely populated settlement of Petukangan Utara Village. The reason for cooperating with Rumah Yatim is because children are the most vulnerable group to become victims. It is hoped that campus activism through fairy tales in developing socialization of fire disaster mitigation from an early age can contribute to increasing disaster literacy and preventing fire threats in densely populated areas of the Jakarta Region